Theoretical foundations of institutional change in land management under conditions of Ukraine’s European integration, the legal regime of martial law, and for the purposes of post-war recovery - Dorosh, Y.; Ibatullin, Sh.; Sakal, O.; Krupin, V.; Kharytonenko, Roman; Derkulskyi, R. (Land Management, Cadastre and Land Monitoring, 2025)
The transformation of Ukraine’s land legislation in connection with integration into the European Union is significantly complicated by the legal regime of martial law and requires, among other things, consideration of the tasks and priorities of the country’s post-war reconstruction. In this context, institutional changes are taking place aimed at improving land resources governance and mitigating the full range of risks in this sphere. However, these processes lack a unified methodological foundation, which threatens their overall success. This article is devoted to substantiating the theoretical foundations of institutional change in the field of land resource governance in accordance with the theory of change approach, using the Grassroots Development Framework and an integrated human rights-based approach, in particular the right of access to land. To identify the key points of institutional changes, the study involved the analysis of the main requirements of the European Union legislation concerning land, the examination of national land legislation and the impact of the legal regime of martial law on it, as well as the assessment of the needs and goals of post-war reconstruction. It is demonstrated that the legal regime of martial law in Ukraine significantly affects institutional changes and institutional support for land management, necessitating temporary adjustments to legal and organizational mechanisms for land resources governance. It is substantiated that, during post-war recovery, institutional changes in land management become critically important and fundamental for effective land resources governance and ensuring food, technological, economic security, and access to land. Major challenges include the restoration of destroyed infrastructure, demining, and the return of lands to productive use. Meanwhile, the design of a strategic agricultural development plan, aligned with European principles and the European Union Common Agricultural Policy, provides opportunities to improve the land management system. A robust and coherent theoretical and methodological framework for the institutional changes taking place in the field of land management and land resources governance in Ukraine will make it possible to plan transformations strategically, thereby aligning and monitoring objectives and outcomes at both the European Union and national levels, in the current period and in addressing post-war challenges related to land use and agricultural development. Keywords: land management, land resources governance, institutional changes, theory of change, European integration, martial law, post-war recovery, right to land, food security.